Beat frequency of cilia from sites of purulent infection. Issue 6 (June 1986) - Wilson, R; Sykes, D A; Currie, D; Cole, P J
Abstract : Mucociliary clearance depends on the interaction between cilia and mucus; it is delayed in the presence of purulent secretions. Nasal mucociliary clearance was examined by the saccharin method and nasal ciliary beat frequency by a photometric technique. Four groups were studied: normal controls, patients with bronchiectasis without nasal symptoms, patients with chronic mucopurulent sinusitis alone, and patients with chronic mucopurulent sinusitis and bronchiectasis. Nasal mucociliary clearance was prolonged in infected patients. Cilia obtained from the site of purulent secretions were found to beat more slowly in vitro (mucopurulent sinusitis 12.1 Hz, mucopurulent sinusitis and bronchiectasis 11.6 Hz), than those obtained from normal controls (14.3 Hz) and from patients with bronchiectasis alone (13.6 Hz). The cause of the ciliary slowing seemed most likely to be the release of host factors during the inflammatory response, rather than the particular organism isolated. Ciliary slowing may contribute to the observed delay of mucociliary clearance in conditions in which purulent secretions are present.